The relationship between shame and guilt - Grey, Ian (2018)
The current study examines whether proneness to shame and guilt is related to the cultural dimensions of collectivism and individualism. Two groups of participants from Ireland (n = 120) and the United Arab Emirates (UAE) (n = 115) completed measures assessing collectivism, individualism, and shame and guilt proneness. Results indicated that both samples displayed similar levels of individualism and collectivism. The UAE sample reported significantly higher levels of guilt proneness and shame proneness characterised by negative self-evaluation. In contrast, the Irish sample displayed significantly higher levels of shame characterised by withdrawal tendencies. Guilt was positively correlated with individualism, but shame was not correlated with either scores on collectivism or individualism. Young Arab women appear to experience higher levels of guilt and shame characterised by negative self-evaluation in comparison to their Irish counterparts who displayed higher levels of guilt proneness.